PSYCHOLOGICAL MORBIDITY AMONG PRIMARY CARE ATTENDEES IN EARTHQUAKE AFFECTED AREAS OF NORTHERN PAKISTAN AND AZAD KASHMIR - Ahmer, Syed; Naqvi, Haider; Khan, Muhammad Kamran; Siddiqui, Naim; Khan, Murad Moosa (Journal of Pakistan Psychiatric Society, 2006)
Objective: The aim of this study was to determine the prevalence of psychiatric morbidity in patients presenting to Primary Healthcare Centers in the affected regions of Pakistan and Azad Kashmir, in the aftermath of the October 8, 2005 earthquake. Another objective was to carry out a need-assessment survey from patients’ and health care providers’ perspective. Design: Observational study. Place & duration of study: The study was carried out in Arja and Muzaffarabad in Azad Kashmir, and Garhi Habibullah in North West Frontier Province in Pakistan, over a period of three weeks. Subjects & Methods: A sample of patients visiting primary care centers in the above mentioned areas was enrolled by convenient method of sampling. Data was collected on a specially designed data collection form. Psychiatric diagnoses were based on ICD-10 diagnostic criteria. Results: 140 patients participated in this study. The median age of the patients seen in the study was 32 years (Age range; 1-73 years), and an inter-quartile range of 21-40 years. Males and females were represented almost equally (51% and 49% respectively). More were married (67%) than single (31 %). In our sample 30 % patients were diagnosed with Depressive disorder and 16% with Generalized Anxiety Disorder. Eighty one percent reported having suffered loss of property, 48% had suffered an injury during the earthquake and 21% reported loss of a family member. Treatment and shelter were identified as the most important needs both by the patients themselves and their primary care physicians. Conclusion: Five months after the earth quake most common psychiatric morbidity was Depression followed by Generalized Anxiety Disorder in primary care attendees in earthquake affected areas. PTSD was conspicuously absent despite the fact that all the participants had suffered significant losses. This needs to be taken into consideration when the plans for physical, psychological and social rehabilitation for this population are made. Key words: Primary care, Depression, Anxiety, PTSD.